Application of Expert System in Diagnosing Polycystic Ovary Syndrome - Bahagia Tarigan (INFOKUM, 2021)
PCOS (Polycystic Ovary Syndrome) or polycystic ovary syndrome is a condition of impaired ovarian function in women of childbearing age. This condition causes the hormones of women suffering from PCOS to become imbalanced due to unknown reasons. The early signs of PCOS are irregular ovulation or fertility, increased levels of male hormones (androgens) in a woman's body, and the appearance of many cysts (fluid-filled sacs) on the ovaries. Things like that are very feared by women because women's nature is to conceive and have offspring, if it is not taken care of from the start or early on, it is not impossible for this to happen. But in fact, public knowledge is still low about Polycystic Ovary Syndrome, information about Polycystic Ovary Syndrome is still not well socialized to the public so that people still do not know how to handle and treat it. In diagnosing Polycystic Ovary Syndrome, there are several methods that can be used, including the Dempster Shafer method. From the results of the study, it can be concluded, among others: The expert system built can provide convenience for users to diagnose polycystic ovary syndrome, and can provide treatment solutions for the disease. The results of the diagnosis using the Dempster Shafer method have a better percentage value.